LINGUOCULTUROLOGICAL ASPECTS OF PROVERBS AND TEACHING ENGLISH THROUGH PROVERBS - Ernazarova Hilola Ergashevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Proverbs are part of folklore in literature. Moreover, they illustrate all characteristics of a nation. So, they are very essential to use during the lesson. The purpose of the article is to illustrate linguculturological aspects of proverbs and usage of them at school to improve students knowledge.